2004
DOI: 10.4314/wsa.v30i2.5065
|View full text |Cite
|
Sign up to set email alerts
|

Random survey of the microbial quality of bottled water in South Africa

Abstract: Due to the increased demand and consumption of bottled water in South Africa, there has been a growing concern about the microbiological quality of this product. Retail outlets sell local as well as imported bottled water to consumers. The microbiological quality of 10 different (8 local and 2 imported) bottled water products were tested over a period of three months on days 1, 30 and 90. Tests for the detection of heterotrophic plate count (HPC) bacteria, total and faecal coliform bacteria, spore-forming Clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
1
15
1
Order By: Relevance
“…The results obtained in this study were comparable and in agreement with similar reports by other researchers such as Obiri-Danso et al [10] and Ehlers et al [21], which indicates that bottled water generally met the criteria set by the WHO on drinking water quality. However, more extensive surveillance of bottled water industries and more stringent regulations should be developed and enforced to ensure that the standards recorded in this study are maintained.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The results obtained in this study were comparable and in agreement with similar reports by other researchers such as Obiri-Danso et al [10] and Ehlers et al [21], which indicates that bottled water generally met the criteria set by the WHO on drinking water quality. However, more extensive surveillance of bottled water industries and more stringent regulations should be developed and enforced to ensure that the standards recorded in this study are maintained.…”
Section: Resultssupporting
confidence: 83%
“…Microbial numbers may reach a peak after a week of storage and remain fairly constant thereafter [2]. In a random survey of microbial quality of bottled water in South Africa, samples from 10 different brands of bottled water were tested over a period of 3 months duration and although total and faecal coliform were not detected, HPC showed a slight variation during the three-month period [21]. Other studies have shown that high counts of E.coli in bottled water could not be detected within four days [22].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the presence of faecal contamination at these samples, thereby giving an indication concerns over the bacteriological quality of sachet water on sales in Owerri, Imo State, Nigeria. This deviate from what was somewhat reported elsewhere in and outside Nigeria by some authors (Ehlers et al, 2004;Anunobi et al, 2006;Abayasekara et al, 2007;Prasanna and Reddy, 2009;Kuitcha et al, 2010;Khaniki et al, 2010). It is important to identify if sachet water is contaminated and to prevent the consumption of these samples (Khaniki et al, 2010).…”
Section: Discussioncontrasting
confidence: 65%
“…A study conducted in Bulawayo reported that, total viable counts where in the range 104 to 151 cfu/ml which is above the bottled water standard of < 100 cfu/ml (Okagbue et al, 2002). In a study conducted in South Africa, HPC were < 100 cfu/ml for most bottled water brands tested, though, one brand of was found to have HPC as high as 2.58 x 10 3 to 1.31 x 10 4 cfu/ml (Ehlers et al, 2004).…”
Section: Resultsmentioning
confidence: 93%